RAPE PRODUCTION AND ITS GEOGRAPHICAL CONCENTRATION IN ROMANIA - Agatha POPESCU; Toma Adrian DINU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the concentration of rape cultivated area and seed production in Romania in the period 2009-2018. using Herfindahl-Hirchman Index (HHI) and Gini -Struck Index (GSI), as well the regression and correlation between these indicators. In 2018, Romania had 633 thousand ha cultivated with rape and produced 1,673,327 tons seeds, 2.8 times more than in 2009. All the eight micro-regions are involved in rape cropping. but the largest surfaces are situated in the S Muntenia (39.07%), S E (24.69), S West Oltenia (10.03), West (9.07%). The highest contribution to rape seed output is given by S Muntenia (42.36%), S East (22.89%), West (11.33) and N East (6.43%). The HHI values > 0.25 reflected a relative high concentration of the cultivated area and seed production, mainly in four micro-regions: S Muntenia, S East, S West Oltenia and West. The Gini-Struck Index indicated a moderate concentration of the cultivated area and also of the seeds production, GS= 0.371- 0.468 for surface, and GS= 0.379- 0.477 for production. The correlation coefficient r = 0.888 proved a positive and strong relationship between the two indicators, and the regression model, Y = 2.694 X - 163.83 reflected that one thousand more ha cultivated with rape will produce 2.534 thousand tons seeds in addition. Rape production is expected to continue to grow and to be more concentrated in the micro-regions mentioned above.